Consumption, apparent digestibility and nutrient balance of diets with bovine milk whey for goats - Araújo, Alexandre Ribeiro; Muir, James Pierre; Vasconcelos, Angela Maria de; Pompeu, Roberto Cláudio Fernandes Franco; Guedes, Luciana Freitas; Costa, Clésio Santos; Carneiro, Maria Socorro de Sousa; Campos, Warley Éfrem; Rogério, Marcos Cláudio Pinheiro (Semina: Ciências Agrárias, 2020)
Increasing milk production in countries such as Brazil, India and Pakistan implies the generation of dairy by-products such as nutrient-rich bovine whey which, if used in feeding small ruminants would reduce environmental waste and add value to this by-product. Twenty entire male kids weighing an average 17 kg and 5 months age were used. The diet control was composed by Aruana hay, milled whole maize, pelleted soybean and limestone. Bovine cheese whey at 1.5; 3.0 and 4.5% (DM basis) was added to experimental diets. Variables measured included intake, nutrient apparent digestibility, energy balance, and nitrogen balance. Regression equations and Pearson correlations (P ? 0.05) were determined. The 3% diet resulted in greater ether extract (EE) (g/kg0.75) and digestible EE (P ? 0.05) concentrations compared to 0% whey. The consumption of cellulose (g/kg0.75) was greater (P ? 0.05) for kids on the 3.0% diet compared to 0 or 1.5%. Nutrient apparent digestibility was not affected (P > 0.05) by the inclusion of whey. Kids on the 4.5% diet excreted more (P ? 0.05) fecal N than those fed no whey; these also retained less N (P ? 0.05) compared to animals fed 3.0% or less whey in their diet. All diets resulted in positive energy and nitrogen balances. Bovine whey can be included in male kid diets up to 4.5% of diet without negatively affecting consumption or apparent digestibility of those diets.